Differences effect of red and big white ginger extract as anti-inflammatory agents by In vitro - Eduardus Bimo Aksono Herupradoto, - (National Academy of Agricultural sciences, NAAS, India., 2022)
This research was conducted to evaluate the possibility of different anti-inflammatory effects from the extract of red ginger and big white ginger by measuring their protein (bovine serum albumin) denaturation inhibitory capability. This study is a quasi experimental, using a model reaction between 0.2 % BSA were heated to form protein denaturation by five groups: red ginger water extract group, red ginger ethanol extract group, big white ginger water extract group, and big white ginger ethanol extract group as the test group (200 ppm, 100 ppm, 10 ppm, and 1 ppm) and diclofenac sodium as the standard group (40 ppm, 20 ppm, 10 ppm, 5 ppm, 2.5 ppm, and 1.3 ppm). Potential inhibition of protein denaturation is known to determine the value of IC50. The results of this study indicate that the red ginger water extract has the IC50 value of 107.4513 ppm (r=0.967), the red ginger ethanol extract has the IC50 value of 193.4338 ppm (r=0.959), the big white ginger water extract has the IC50 value 160 ppm (r=0.969), the big white ginger ethanol extract has the IC50 value 160.9536 ppm (r=0.994), of whereas for diclofenac sodium by 27.1133 ppm (r=0.874). These results indicate that the red ginger and big white ginger as a potential inhibitor of protein denaturation for inflammatory processes in vitro.